2009
DOI: 10.1213/ane.0b013e3181bce58d
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Position Influence the Reading of the Bispectral Index Monitor?

Abstract: Changing a patient's position significantly affects the BIS values, which might affect the interpretation of anesthetic depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Kaki and Almarakbi [2] reported a position-related change in BIS readings. They observed significant increase in BIS values in the head-down position compared with the supine position, whereas the head-up position significantly decreased BIS compared with the supine position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaki and Almarakbi [2] reported a position-related change in BIS readings. They observed significant increase in BIS values in the head-down position compared with the supine position, whereas the head-up position significantly decreased BIS compared with the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative monitoring of the depth of anesthetic is important to prevent this problem. Use of the bispectral index (BIS) reduces the cases of intraoperative awareness [2,3,4]. The BIS is a single number calculated from electroencephalogram (EEG)-derived sub-parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors consider BIS monitoring inappropriate in the present setting. Patient position has been shown to influence BIS monitoring17, 18, and, as extreme position changes are common during laparoscopic gastric bypass surgery, BIS values may be difficult to interpret. In addition, Dahaba19 has reported that BIS values are not the same for equipotent concentrations of different inhaled anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Patient position was also found to affect BIS values [57], like for example positioning the patient from neutral (supine) to head down the BIS increased, whereas it decreased when positioning the patient's head up. Once more, these changes in pEEG index were probably caused by changes in brain perfusion with the increase and decrease the authors found in mean arterial pressure during head down and head up positions, respectively.…”
Section: Patient Condition and Intraoperative Eventsmentioning
confidence: 99%